The role of diabetes-associated autoantibodies in confirming the diagnosis of type 1 diabetes mellitus in children and adolescents - Gazali, Ahmad Mahfuz (Innoquest Pathology Sdn. Bhd., 2023)
Type 1 diabetes mellitus (T1DM) is a chronic condition caused by immune cell infiltration and destruction of the pancreas insulin-producing beta (β) cells. The death of β cells causes the loss of insulin secretion, causing hyperglycaemia. The Malaysian Diabetes in Children and Adolescents Registry published a report in 2007 stating that almost 70% of childhood and adolescent diabetes were T1DM patients.